Percutaneous Coronary Intervention as Clinical Outcome Predictor for in-Hospital Adverse Events in STEMI Patients - Anita Surya Santoso; Mohammad Saifur Rohman; Ardian Rizal; Setyasih Anjarwani; Heny Martini; Indra Prasetya (Heart Science Journal, 2022)
Background : Limited resources and the concurrent COVID19 pandemic hinders the appropriate time to achieve reperfusion in Infarct-related artery (IRA). The number of patients receiving late primary PCI (PPCI) and without revascularization are steadily increase within 2 years into the pandemic. The impact of PCI timing in this setting has not been fully elucidated.Objective : This study was conducted to evaluate the effect of early PPCI vs late PPCI vs non revascularization groups towards in-hospital mortality and complications. This study also aimed to determine whether PPCI is the main predictor for in-hospital adverse events in STEMI patients.Method : Data of STEMI patients registered in Saiful Anwar General Hospiital ACS registry were collected between 2018-2021 Patients were subdivided into early PPCI if receiving PCI within the recommended time of the 2017 ESC STEMI management guideline, late PPCI if receiving PCI outside the timeframe provided by the guideline, and optimal medical therapy group if not receiving any means of revascularization. Patients undergoing thrombolysis were excluded. Afterwards, the incidence of in-hospital adverse event were calculated as primary endpoints, development of immediate complications during hospitalizations were analyzed as secondary endpoints. Stratification of baseline characteristics and PCI categorizations were performed using multivariate analysis to determine the main predictor of in-hospital mortality between STEMI patients.Results :  568 STEMI patients were included in the study with 387 in early PPCI, 107 in late PPCI, and 74 in optimal medical therapy group. Incidence of in-hospital mortality were significantly higher in optimal medical therapy group and lowest in early PPCI group (32.4% and 7.5% respectively, P 0.00). Mortality odds ratio between early PPCI group and optimal medical therapy group were significantly lowest (OR 0.17, 95% CI 0.13 – 0.41). Complications between each treatment groups were significantly different with early PPCI had the lowest incidence of in-hospital complications of cardiogenic shock, cardiac arrest, and VT/VF. Stratification of baseline characteristics and PCI category reveals that timing PPCI is the main predictor for in-hospital adverse events (HR 4.506, 95% CI 2.487-6.662, P 0.00). Conclusion : Percutaneous coronary intervention is the main predictor for the incidence of in hospital mortality and complications in STEMI patients.Keyword : STEMI, PCI, mortality, complications, in-hospital adverse events.